KEDUDUKAN HUKUM KORBAN SEBAGAI SUBJEK DALAM SISTEM PERADILAN PIDANA INDONESIA: ANTARA VIKTIMOLOGI DAN PEMBARUAN KEBIJAKAN PIDANA - Nur Adillah, Roja; Masita Sari, Devi; Krismen, Yudi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Indonesia's criminal justice system has historically marginalized victims, treating them merely as witnesses serving the state's interest in proving offenders' guilt. Yet victims are the parties most directly harmed by criminal acts. This study examines the legal standing of victims as independent subjects within Indonesia's criminal justice system from the perspective of victimology and criminal law reform policy. Using normative legal research with statutory, conceptual, and comparative approaches, the findings reveal that normative provisions on victims' rights remain scattered, unsystematic, and have not positioned victims as autonomous legal subjects at every stage of criminal proceedings. A significant normative gap exists between modern victimological concepts and Indonesia's positive law construction. Reforms through the 2023 Penal Code and the 2022 Correctional Law have not adequately addressed the need for comprehensive integration of victims' legal standing. Normative reconstruction within the draft Criminal Procedure Code is needed to provide victims with concrete procedural rights at every sub-system of the criminal justice process.